Residual Mild Varus Alignment and Neutral Mechanical Alignment Have Similar Outcome after Total Knee Arthroplasty for Varus Osteoarthritis in Five-Year Follow-Up - Zhang, Zhiqi; Liu, Can; Li, Zhiwen; Wu, Peihui; Hu, Shu; Liao, Weiming (The Journal of Knee Surgery, 2020)
The effect of residual varus on survival rate and function in patients with varus knee osteoarthritis (OA) was considered an important issue for successful primary total knee arthroplasty (TKA). In this study, we compared the midterm clinical and functional outcomes in patients with different residual varus. A retrospective review of 175 patients (219 knees) with varus OA was > 3° for the hip-knee-ankle (HKA) who underwent primary TKA after exclusions and loss to follow-up from 237 patients (281 knees). The mean follow-up period was 5.2 ( ±  1.1) years. Patients were divided into four groups according to the first postoperative HKA angle from weight-bearing full-leg radiographs: “valgus” group (HKA angle > 0°, n = 44), “neutral” group (–3° ≤ HKA angle < 0°, n = 86), “mild varus” group (–6° ≤ HKA angle < –3°, n = 62), and “severe varus” group (HKA angle < –6°, n = 27). Survival analysis, Knee Society Score (KSS, including knee score and functional score), and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) were compared among the four groups. No knee required revision surgery during follow-up. For the KSS knee score and functional score at the last follow-up, the neutral and mild varus groups were better compared with the valgus and severe varus groups (p < 0.05), and there were no significant differences between the neutral and mild varus groups (p > 0.05). WOMAC scores of the neutral and mild varus groups were also better compared with the valgus and severe varus groups (p < 0.05), and there were no significant differences between the neutral and mild varus groups at the last follow-up. The postoperative HKA angle was significantly changed in valgus group between first and at the last follow-up when compared with the other three groups (p < 0.05). Leaving an HKA angle at < 6° varus had the same excellent functional outcome as neutral mechanical alignment after TKA for varus-type OA in the 5-year follow-up, using mechanically aligned technique. Caution is advised when leaving valgus or leaving severe varus after TKA.
Keywords: TKA; varus alignment; osteoarthritis